Foreign and Familiar: Recruitment Pathways of Young People Engaged With Extremism in Australia - Campion, Kristy (Perspectives on terrorism, 2024)
It has been established by leaders of the Australian national security community, such as the Australian Security Intelligence Organisation and the Australian Federal Police, that young people are being increasingly recruited into extremism. To date, few Australian studies have examined this issue using primary source data. This article seeks to understand the conditions which may make vulnerable young Australians more susceptible to recruitment, recruitment pathways, and forms of recruitment. To address this, primary sources were consulted, and frontline countering violent extremism (CVE) practitioners were interviewed. It was found that there is no typical pathway for young Australians to be recruited to extremism and that recruitment can be both foreign (informed by transnational networks and organisations) and/or familiar (within the immediate domestic environment of the young person). We identified the continued significance of online vectors, but further established the ongoing relevance and power of offline engagement for the recruitment of young people. Finally, we suggest that multiple intersecting vulnerabilities render young people more susceptible to recruitment, with data that suggests they may be naïve to their being recruited in the first place.